2010
DOI: 10.1152/ajpregu.00764.2009
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral inhibition of AT1a receptors in the paraventricular nucleus inhibits acute increases in mean arterial blood pressure in the rat

Abstract: Brain and peripheral renin-angiotensin systems are important in blood pressure maintenance. Circulating ANG II stimulates brain RAS to contribute to the increase mean arterial pressure (MAP). This mechanism has not been fully clarified, so it was hypothesized that reducing angiotensin type 1a (AT 1a) receptors (AT1aRs) in the paraventricular nucleus (PVN) would diminish intravenous ANG II-induced increases in MAP. Adenoviruses (Ad) encoding AT 1a small hairpin RNA (shRNA) or Ad-LacZ (marker gene) were injecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…In the hypothalamus, the paraventricular nucleus (PVN) has been considered as a regulatory centre of the central sympatho-adrenomedullary outflow4344. Actually, microinjected AngII into the PVN increased mean blood pressure45 and specific knockdown of AT 1a receptors in the PVN by infusion of interfering RNA against the receptors prevents hypertension induced by AngII treated peripherally4647. These findings suggest a possibility that the angiotensinergic system in the PVN is critical for AngII-induced elevation of blood pressure and also for the central sympatho-adrenomedullary outflow.…”
Section: Discussionmentioning
confidence: 99%
“…In the hypothalamus, the paraventricular nucleus (PVN) has been considered as a regulatory centre of the central sympatho-adrenomedullary outflow4344. Actually, microinjected AngII into the PVN increased mean blood pressure45 and specific knockdown of AT 1a receptors in the PVN by infusion of interfering RNA against the receptors prevents hypertension induced by AngII treated peripherally4647. These findings suggest a possibility that the angiotensinergic system in the PVN is critical for AngII-induced elevation of blood pressure and also for the central sympatho-adrenomedullary outflow.…”
Section: Discussionmentioning
confidence: 99%
“…12 It was reported that adenoviruses encoding AT 1a small hairpin (shRNA) in the PVN in normal rats blunted the acute Ang II-induced elevation in MAP, but had no significant effect on basal MAP. 14 We speculate that the enhanced AT 1a R activity in the PVN has an important pathogenical role in triggering and sustaining the hypertension.…”
Section: Discussionmentioning
confidence: 82%
“…13 Microinjection of adenoviruses encoding AT 1a R small hairpin RNA into the PVN inhibits acute increases in arterial blood pressure but had no significant effects on the basal arterial pressure in normal rats. 14 However, it remains unknown whether gene silence of the AT 1a R in the PVN has beneficial effects on hypertension. The present study was designed to determine whether silencing of the AT 1a R in the PVN by artificial microRNA (amiRNA) interference attenuates the hypertension and sympathetic activity, and improves the cardiovascular remodeling in SHR.…”
Section: Introductionmentioning
confidence: 99%
“…A: PVN adenoviral (Ad) eNOS administration had no effect on baseline blood pressure (V1-V6); however, Ad eNOS-treated wrap rats had a significantly blunted increase in blood pressure (days 0 -30). In addition, wrap Ad eNOS-treated rats were not significantly different from sham animals at the beginning of the treatment protocol (days 0 -3) or at the conclusion of the experiment (days [23][24][25][26][27][28][29][30]. B: PVN Ad eNOS administration had no effect on baseline blood pressure (V1-V6); however, during the beginning of the sham/renal wrap protocol, there was a significant difference in heart rate (days 2-5) in wrap Ad eNOS-treated rats compared with wrap Ad LacZ-treated rats.…”
Section: Discussionmentioning
confidence: 88%
“…These experiments confirmed that eNOS was expressed within the PVN in Ad eNOS-treated rats; however, due to the nature of limited to no eNOS being present during naive conditions, quantification of expression was not possible. A previous study (28), using an angiotensin type 1 receptor dominant negative Ad, demonstrated specific PVN targeting of Ad viruses.…”
Section: Chronic Increases In Nos and No Availability In The Pvnmentioning
confidence: 91%